THE ROLE OF ISLAMIC BANKS IN ACHIEVING SUSTAINABLE DEVELOPMENT - Assit. Lect. Ali Hussain Hassan; Assist. Prof. Huda Abdulredha Ali (Scholar Express Journals, 2024)
The importance of the research comes from the fact that the subject of Islamic banking is one of the most important forms of Islamic finance that contribute to achieving sustainable economic development through green financing, spreading savings awareness among individuals, and rationalizing the spending behavior of the broad base of people with the aim of mobilizing surplus economic resources and idle capital, attracting them and employing them in a sound economic base. Stable and compatible with Islamic Sharia, making optimal use of it, and inventing new formulas that are compatible with Islamic Sharia. The research aims to identify the basic and theoretical concepts of Islamic banks and their importance, and to analyze the role of these banks in supporting and encouraging investment in order to achieve sustainable development. The research reached the conclusion that Islamic banks play an important role in stimulating investment through their function of granting loans, which is interest-free qard hassan (usury), to investment projects to support the productive capacity of the national economy, in addition to spreading savings awareness among individuals and rationalizing spending behavior with the aim of mobilizing resources. economy and employing idle capital and thus achieving sustainable development.The research recommends: working to spread more awareness and Islamic culture related to the concepts and terminology of Islamic banking that contribute to attracting local and foreign investments in accordance with the Islamic Sharia approach
Keywords: Islamic Banks; Sustainable Development; Interest; Free Bank